PENERAPAN PROGRAM INTERVENSI STUNTING PADA BALITA DAN IBU HAMIL DENGAN PEMBERDAYAAN MASYARAKAT - Rumintan Tampubolon; Elina Latifahny; Misrawati; Wisnu Aditia Wardana Ginting; Sofia Yulidar Hafni; Nurul Rahmawati; Alrasimah; Puspa Sari; Putri Ayuni; Dynda Tri Azrina; Annisa Rahman (Stikes Yarsi Mataram, 2023)
Stunting is a problem of nutritional status that is less chronic in nature during the growth and development of toddlers. One of the direct causes of stunting is nutritional intake. One effort to eradicate stunting is through community service activities by implementing a stunting intervention program to prevent stunting from an early age. The purpose of this community service is to identify health problems that arise, especially in toddlers and pregnant women through nursing assessments with community empowerment. The stunting intervention program carried out included counseling on stunting prevention, demonstrating supplementary feeding, development stimulation counseling and community empowerment by providing high protein supplemental food to 4 toddlers at risk of stunting. Evaluation of this activity was carried out by giving post-test sheets to respondents after the counseling intervention and measuring weight with a weighing device for 4 toddlers who were the target of stunting risk for the results of the high-protein food intervention. The results obtained were that there was an increase in respondents' knowledge after participating in stunting counseling activities> 39%, an increase in respondents' knowledge after participating in counseling activities for providing additional food, namely as much as 47%, an increase in respondents' knowledge after participating in counseling activities on stimulation of toddler development 40%, and weight gain in toddlers reaches 75%.